'Struggles as engagement' in teacher change: a longitudinal case study of a reading teacher's changing practices. Issue 4 (19th May 2019) - Ng, Clarence; Leicht, Alysse
ABSTRACT: Teacher change involves the transformation of beliefs, knowledge and practices. While research has highlighted significant facilitative conditions as well as barriers to these changes, insufficient attention has been devoted to examining influences derived from existing practices perpetuated by institutional factors and teachers' personal histories and experiences. This paper reports on an Australian teacher's struggles while engaging in the adoption of an innovative reading practice using a student-led and collaborative design for promoting reading engagement among economically disadvantaged students in an Australian primary school. A within-method triangulation approach for data analysis was adopted using a longitudinal data set containing teacher interviews, classroom observations, videotaped intervention lessons, student interviews, and field notes accumulated over an academic year. Based on an activity theoretic perspective, the teacher's struggles were derived from conflicting ideas and dilemmas associated with the roles of participants (teacher, student and researcher), beliefs held regarding the purposes of reading education and contradictions between existing and new practices. This qualitative case study is significant because it draws research attention away from the teacher's professional attributes to incompatibilities between old and new practices and the ensuing struggles throughout the change process. Addressing these potential struggles facilitates not just a change in teacher knowledge but also the abandonment of old practices and adoption of new approaches.